Transcription factor Bcl11b sustains iNKT1 and iNKT2 cell programs, restricts iNKT17 cell program, and governs iNKT cell survival - Uddin, Mohammad Nizam (Proc Natl Acad Sci U S A, 2016)
Invariant natural killer T (iNKT) cells are innate-like T cells that recognize glycolipid antigens and play critical roles in regulation of immune responses. Based on expression of the transcription factors (TFs) Tbet, Plzf, and Rorγt, iNKT cells have been classified in effector subsets that emerge in the thymus, namely, iNKT1, iNKT2, and iNKT17. Deficiency in the TF Bcl11b in double-positive (DP) thymocytes has been shown to cause absence of iNKT cells in the thymus and periphery due to defective self glycolipid processing and presentation by DP thymocytes and undefined intrinsic alterations in iNKT precursors. We used a model of cre-mediated postselection deletion of Bcl11b in iNKT cells to determine its intrinsic role in these cells. We found that Bcl11b is expressed equivalently in all three effector iNKT subsets, and its removal caused a reduction in the numbers of iNKT1 and iNKT2 cells, but not in the numbers of iNKT17 cells. Additionally, we show that Bcl11b sustains subset-specific cytokine production by iNKT1 and iNKT2 cells and restricts expression of iNKT17 genes in iNKT1 and iNKT2 subsets, overall restraining the iNKT17 program in iNKT cells. The total numbers of iNKT cells were reduced in the absence of Bcl11b both in the thymus and periphery, associated with the decrease in iNKT1 and iNKT2 cell numbers and decrease in survival, related to changes in survival/apoptosis genes. Thus, these results extend our understanding of the role of Bcl11b in iNKT cells beyond their selection and demonstrate that Bcl11b is a key regulator of iNKT effector subsets, their function, identity, and survival.